Effects of cryo-facial mask on running performance in amateur middle-distance runners - Massimo De Nardi; Luca Filipas; Simone Di Gennaro; Silvia Allemano; Gabriele Gallo; Andrea Meloni; Lucio Della Guardia; Livio Luzi; Antonio La Torre; Roberto Codella (Cryobiology, 2024)

Power output at the moderate-to-heavy intensity transition decreases in a non-linear fashion during prolonged exercise - Gabriele Gallo; Emanuela Luisa Faelli; Piero Ruggeri; Luca Filipas; Roberto Codella; Daniel J. Plews; Ed Maunder (European Journal of Applied Physiology, 2024)
Purpose The aims of this study were to: (i) describe the time course of the decrease in power output at the moderate-to-heavy intensity transition during prolonged exercise; (ii) investigate the association between durability of the moderate-to-heavy intensity transition and exercise capacity; and (iii) explore physiological correlates of durability of the moderate-to-heavy intensity transition. Methods Twelve trained cyclists (age: 40 ± 8 y, $$\dot{\text{V}}$$ V ˙ O 2 peak: 52.3 ± 5.2 mL·min −1 ·kg −1 ) performed an exhaustive cycling protocol involving alternating incremental exercise tests to determine power output at the moderate-to-heavy intensity transition via the first ventilatory threshold (VT 1 ), and 30-min bouts at 90% of the power output at the previously estimated VT 1 in the rested state. The individual time course of VT 1 was modelled using linear and second-order polynomial functions, and time to a 5% decrease in VT 1 (Δ5%VT 1 ) was estimated using the best-fitting model. Results Power output at VT 1 decreased according to a second-order polynomial function in 11 of 12 participants. Time-to-task failure (234 ± 66 min) was correlated with Δ5%VT 1 (139 ± 78 min, r s = 0.676, p = 0.016), and these were strongly correlated with absolute and relative rates of fat oxidation at specific exercise intensities measured during the incremental test performed in the rested state. Conclusions These data: (i) identify a non-linear time course of decreases in the moderate-to-heavy intensity transition during prolonged exercise; (ii) support the importance of durability of the moderate-to-heavy intensity transition in prolonged exercise capacity; and (iii) suggest durability of the moderate-to-heavy intensity transition is related to fat oxidation rates.

Thermal responses induced by nitrogen and forced convection based partial-body cryostimulation - Massimo De Nardi; Silvia Allemano; Ambra Bisio; Emanuela Faelli; Antonio La Torre; Piero Ruggeri; Roberto Codella (Journal of Thermal Biology, 2023)